2012
DOI: 10.1080/10255842.2012.683429
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a postural change of the swimmer's head in hydrodynamic performances using 3D CFD

Abstract: This study deals with recent researches undertaken by the authors in the field of hydrodynamics of human swimming. The aim of this numerical study was to investigate the flow around the entire swimmer's body. The results presented in this article focus on the combination of a 3D computational fluid dynamics code and the use of the k-ω turbulence model, in the range of Reynolds numbers representative of a swimming level varying from national to international competition. Emphasis is placed on the influence of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 13 publications
(24 reference statements)
1
11
0
2
Order By: Relevance
“…Because of the nonuniformity of the body on the swimmer's head, shoulders, elbows, hips, knees, and buttocks, complex turbulent zones are Computational Fluid Dynamics Method for the Analysis of the Hydrodynamic Performance in Swimming http://dx.doi.org/10.5772/61176 generated around the swimmer's body. In this study, Popa et al [26] noted a recirculation zone on the swimmer's buttocks with a larger recirculation zone when the head is lifted up whatever the head position. The numerical results show that the position of the head plays a very important role for high swimming velocities on the hydrodynamic performances.…”
Section: Streamline Patternsmentioning
confidence: 48%
See 1 more Smart Citation
“…Because of the nonuniformity of the body on the swimmer's head, shoulders, elbows, hips, knees, and buttocks, complex turbulent zones are Computational Fluid Dynamics Method for the Analysis of the Hydrodynamic Performance in Swimming http://dx.doi.org/10.5772/61176 generated around the swimmer's body. In this study, Popa et al [26] noted a recirculation zone on the swimmer's buttocks with a larger recirculation zone when the head is lifted up whatever the head position. The numerical results show that the position of the head plays a very important role for high swimming velocities on the hydrodynamic performances.…”
Section: Streamline Patternsmentioning
confidence: 48%
“…Popa et al [26] showed in Figure 11 streamline patterns to highlight the flow structure around the swimmer's neck, chin, and buttocks for each of the three head positions and for a velocity of 3.1 m/s. One may observe recirculation zones around the swimmer's neck, chin, and buttocks according to the position of the head.…”
Section: Streamline Patternsmentioning
confidence: 99%
“…During these phases, the position of the head is of fundamental importance because it determines the dynamics of the impact of the body with the fluid and the vortexes that propagate along the swimmer's body (9,10,15). Swim caps could affect these factors and thus could have an impact on swimming performance (5).…”
Section: Discussionmentioning
confidence: 99%
“…Studies using computational fluid dynamics indeed have shown that the position of the head has a marked influence on Dp, strongly modifying the wake around the swimmer (9,10,15). Moreover, Marinho et al (5) have shown that a reduction of Dp of up to 15% can be obtained by wearing a swim cap (compared with the "no-cap" condition), even if this "intervention" affects a very small surface of the swimmer's body.…”
Section: Introductionmentioning
confidence: 96%
“…In swimming, this methodology has been used to study the propulsive forces produced by the hands and forearms [8][9][10] and the legs during swimming, 11,12 as well as the magnitude of the drag forces resisting forward motion. [13][14][15] With respect to propulsive forces, CFD can provide insight into basic issues concerning swimming technique that, based on the knowledge provided by experimental approaches, remain unclear or, at least, controversial. The relative position of the fingers and thumb during the underwater path of the stroke cycle is one of these issues.…”
mentioning
confidence: 99%